1993
DOI: 10.3382/ps.0721548
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Kidney During Reproduction: Role of Estrogen in the Regulation of Responsiveness to Parathyroid Hormone

Abstract: Avian kidney function adapts during reproduction to provide the calcium required for eggshell formation. Adaptive changes in kidney function are 1) increased parathyroid hormone (PTH)-dependent adenylate cyclase activity; 2) elevated numbers of PTH receptors; and 3) increased synthesis of 1,25-dihydroxycholecalciferol. Because exogenous estrogen mimics these changes, this study explored the physiological role of estrogen in the regulation of kidney function by altering egg-laying status or levels of estradiol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Therefore, it may be concluded that plasma Ca levels of laying hens is a strong regulator of this enzymatic system. This conclusion is in agreement with previous reports (Bar et al, 1978;Forte et al, 1983;Armbrecht and Forte, 1985;Martz et al, 1985;Elaroussi et al, 1993).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Therefore, it may be concluded that plasma Ca levels of laying hens is a strong regulator of this enzymatic system. This conclusion is in agreement with previous reports (Bar et al, 1978;Forte et al, 1983;Armbrecht and Forte, 1985;Martz et al, 1985;Elaroussi et al, 1993).…”
Section: Discussionsupporting
confidence: 95%
“…During reproductive activity in the female chicken, endogenous estrogen mediates changes in the function of the kidney that involve the two major Caregulating hormones: PTH and 1,25 (OH) 2 D 3 (Elaroussi et al, 1993). The number of PTH receptor sites and the activity of PTH-dependent adenylate cyclase are elevated in the kidney of mature egglaying females, relative to either the mature male or immature chicken of either sex (Forte et al, 1983).…”
Section: Introductionmentioning
confidence: 98%
“…It increases the calcium concentration in the blood serum by stimulating the kidneys to secrete an enzyme (1α-hydroxylase), which works to convert the inactive form of vitamin D (25-hydroxyCholecalcifrol) to form the active form of vitamin D (1.25-dihydroxy Cholecalcifrol) It is important in the absorption of calcium and phosphorous from the mucous membrane of the small intestine through its association with receptors located in the cytoplasm and then its transmission to the nucleus and stimulating the formation of the calcium-binding protein (P. B.Ca), which works to transport and absorb calcium, thus increasing their level in the blood serum. Or, estrogen may stimulate the activity of the enzyme adenylate cyclase in the cell membrane, thus increasing the process of entering the hormone (PTH) Parathormone, which is responsible for regulating calcium and phosphorous levels in the blood and manufacturing the active form of vitamin D, thus increasing its absorption in the duodenum [15][16][17]. Estrogen increases the gene expression of calcitonin in uterine cells to increase the source of calcium deposition processes in the egg shell, [14].…”
Section: Qualitative Characteristics Of Eggsmentioning
confidence: 99%